Antibacterial activity of three essential oils and some monoterpenes against Ralstonia solanacearum phylotype II isolated from potato. (October 2019) - Mohamed, Abeer A.; Behiry, Said I.; Younes, Hosny A.; Ashmawy, Nader A.; Salem, Mohamed Z.M.; Márquez-Molina, Ofelia; Barbabosa-Pilego, Alberto
Abstract: The present study describes the possibility of using some essential oils and monoterpens as bioagents against the growth of Ralstonia solanacearum, a causal bacterium of potato brown rot disease. Eight isolates of the bacterium were recovered from infected potato tubers, showing typical symptoms of the disease, Isolates were identified as R.solanacearum phylotype II, based on biochemical and physiological characteristics, as well as, at the molecular level through PCR analysis. Three essential oils extracted from Corymbia citriodora (leaves), Cupressus sempervirens (aerial parts), and Lantana camara (aerial parts) were evaluated for their antibacterial activity against eight isolates of R. solanacearum phylotype II. Results demonstrated that L. camara essential oil (concentration 5000 μg/mL) had the highest effects against the RsMo2, RsSc1 and Rs48, with inhibition zone (IZ) values of 17.33, 16.33, and 17.50 mm, respectively, also against Rs2 (IZ 14.33 mm), and RsIs2 (IZ 16 mm). C. citriodora oil showed the highest activity against RsBe2 (IZ 14 mm), RsFr4 (IZ 13.66 mm) and RsNe1 (IZ 13.66 mm). Gas Chromatography-Mass Spectrometry (GC-MS-FID) analyzed the chemical composition of these essential oils. It was proved that L. camara leaves contains mainly trans -caryophyllene (16.24%) and α -humulene (9.55%), in C. citriodora oil were α -citronellal (56.55%), α -citronellol (14.89%), and citronellol acetate (13.04%), and in Cup. sempervirens aerial parts were cedrol (22.17%), and Δ3-carene (18.59%). Five monoterpenes were evaluated against the most resistance Ralstonia isolate RsFr5 to the three studied essential oils and found that limonene had the highest effect against it compared with the lowest thymol. The results proved the strong bio effects of the essential oil from L. camara leaves as a natural product contained monoterpenes that can inhibit the growth of tested R. solanacearum phylotype II isolates. Graphical abstract: Image 1 Highlights: Brown rot pathogen, R. solanacearum, was isolated from diseased tuber tissues. R. solanacearum isolates were identified at the molecular level through PCR analysis. Citronellal, limonene, carvone, camphor and thymol had potential activity against RsFr5 isolate. L. camara and C. citriodora essential oils showed good antibacterial activity.